RELATIONSHIPS AND RESPONSIBILITIES OF TEACHING STAFFS TO EXECUTIVE DEVELOPMENT PROGRAMS. - Winslow, Rex S. (The Accounting Review, 1958)
Abstract The article presents views of the author on the place of the accounting faculty, if any, in the work the school may undertake in connection with educational programs for outside businessmen. According to the author, at present the contract with the school calls for the faculty accountant to carry no more than the customary or conventional load, any other work that he does for the school is considered to be a new contract in which the school competes for his free time with other earning possibilities. Now that many schools are accepting a part in the management development movement and are organizing and selling educational programs on a cost-plus basis, they are able, by using the group approach to consulting, to compete with other earning opportunities of the faculty. The group consulting approach has several advantages. It increases the effectiveness of the accountant, it increases the extent of his impact on the business community, it helps the public relations of the business school and more importantly, it changes the outlook and the thinking of the accountant about the accounting function.